Sepsis-Like Systemic Inflammation Induced by Nano-Sized Extracellular Vesicles From Feces - Park, Kyong-Su; Lee, Jaewook; Lee, Changjin; Park, Hyun Taek; Kim, Jung-Wook; Kim, Oh Youn; Kim, Sae Rom; Rådinger, Madeleine; Jung, Hoe-Yune; Park, Jaesung; Lötvall, Jan; Gho, Yong Song (Frontiers in Microbiology, 2018)
Nano-sized extracellular vesicles (EVs), including exosomes, microvesicles, and other types of vesicles, are released by most mammalian cells and bacteria. We here ask whether feces contain EVs of mammalian and/or bacterial origin, and whether these EVs induce systemic inflammation. Fecal extracellular vesicles (fEVs) were isolated from mice and humans. The presence of EVs from Gram-negative and Gram-positive bacteria was detected by enzyme-linked immunosorbent assay using anti-lipid A and anti-lipoteichoic acid antibodies, whereas Western blot using anti-beta-actin antibody was employed to detect host-derived EVs in the fEVs. Further, fEVs were administered into mice by intraperitoneal injection, and inflammatory responses were investigated in the peritoneum, blood, and lungs. The role of TLR2 and TLR4 were studied using knockout mice. Significant quantities of EVs were present in feces from mice as well as humans, and derived from Gram-negative and Gram-positive bacteria, as well as the host. Bacteria-free fEVs introduced into the peritoneum induced local and systemic inflammation (including in the lungs), but fEVs from germ-free animals had weaker effects. This pronounced local and systemic inflammatory responses seemed to be induced by EVs from both Gram-negative and Gram-positive bacteria, and was attenuated in mice lacking TLR2 or TLR4. Our findings show that fEVs cause sepsis-like systemic inflammation, when introduced intraperitoneally, a process regulated by TLR2 and TLR4.